20 A Minap-Like e-registry for the First Time in NHS Scotland? A Proof-of-Concept Report from the Pilot Project. (6th June 2015) - Berry, Colin; Morris, Tamsin; Ross, Karen; Foster, Alan; Flood, Marion; Christie, Jim; Pauline, Elaine; Forbes, Brian; Hatrick, Stewart; Lawson, Brian; Findlay, Iain
Abstract : Background: The Myocardial Ischaemia National Audit Project (MINAP) provides data on national standards of care for patients with myocardial infarction (MI) in England and Wales but not in Scotland. In the West of Scotland (WoS), electronic patient records are being implemented in place of paper records. We aimed to record-link hospital patient episodes using the new e-systems in order to develop a secondary care e-registry for hospitalised patients with an acute coronary syndrome (ACS), including suspected STEMI, NSTEMI or unstable angina (UA). Methods: The systems are (1) Trakcare Patient Admin System with extracts data based on ICD-10 diagnosis codes, (2) SCI-Gateway e-referrals for invasive cardiovascular procedures, (3) a hospital-level integrated patient record including cardiac catheter laboratory data (CATHI), (4) the WoS NHS Safe Haven for healthcare data including hospitalisation and mortality. We implemented a pilot study with data extraction for 1 Oct – 31 Dec 2013 for all admissions with an ICD-10 diagnosis of angina (I200-I209), MI (I210-I229), Other Ischaemic Heart Disease (IHD) (I240-I249), and heart failure (I50). The project involved identification of the NHS referral pathways, case e-record linkage, and quality assurance. Results: The regional ACS network involves 7 acute hospitals in WoS (population 2.2 million) including the Golden Jubilee National Hospital, a regional hub for invasive cardiology. During the 3-month pilot, 930 unique patients had 1090 admissions involving 969 distinct spells (i.e. index admission and early out-patient re-admission for angiography). Of these spells, the final diagnosis was IHD in 775 (80%) patients, including 164 (16.9%) with STEMI, 287 (29.6%) with NSTEMI, 26 (2.7%) with unstable angina, 249 (25.7%) with stable angina, 5 with other IHD (0.5%), 43 (4.4%) with 'other chest pain' and 194 with a non-IHD final diagnosis (20%) (e.g. pericarditis). The pathways were mapped in 100% of the patients including 25.8% admitted directly to the invasive centre, 5.6% via local A&E to the invasive centre, 22.3% via the local hospital followed by in-patient transfer to the invasive centre, 8.9% discharged from the local hospital then readmitted to the invasive centre for planned early out-patient angiography, 4.6% within the local hospital only (no transfer), and 32.8% directly admitted on an elective basis to the invasive centre (non-acute). The mean duration of stay was similar for patients with a diagnosis of STEMI (5.2 days) or NSTEMI (4.6 days), but less for patients with UA (2.2 days) and more for other IHD diagnosis (9.1 days). Data on health outcomes will be presented at the conference. Conclusions: For the first time, the pilot e-Registry has generated MINAP-like data in NHS Scotland. Information on admissions with or without a final ACS diagnosis is collected. NHS Scotland has emerging potential to contribute to MINAP.